Analysis of internal emigration in Poland using the spatial dynamic shift-share method - Lewandowska-Gwarda, Karolina; Antczak, Elżbieta (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
The main aim of this paper is to examine internal population movements in Poland, and in particular, the problems connected with population outflow to other areas of the country. The spatial dynamic shift-share method is used to analyse the internal emigration of the population (deregistrations for permanent stay in other subregions) according to the gender and migration direction (urban, rural) criteria from 2000 to 2012. Therefore, the study analyses the pace of changes in the volume of the phenomenon as well as the share and identification of the structural and regional factors (local, spatial) in the size of the global effect of deregistrations in specific subregions. Moreover, it takes into consideration a spatial weights matrix allowing to include the spatial aspects in the study
Argumenta Oeconomica, 2015, Nr 2 (35), s. 123-143
Keywords: Spatio-temporal analysis; spatial dynamic shift-share; migration; internal emigration